Supplementary Resources Materials in English Language Classrooms: Development and Implementation - Karki, Tek Mani (Tribhuvan University Journal, 2018)
Supplementary resource materials are additional but more useful in English language teaching (ELT). The teacher needs to supplement materials to promote motivation, which is one of the key factors influencing learning. However, there is a lack of study what supporting materials the teachers are using in English language classrooms for teaching learning purposes. This paper attempts to explore the supplementary teaching materials selected and used in ELT classrooms of community schools in Nepal. The information was collected through observations, interviews and focus group discussion. It was found that non-technical visual supplementary teaching materials were used more than technical and audio/audio visual ones. Most of the materials were used for reading and writing purposes. Teachers’ knowledge about technology, carefulness in using appropriate instructional materials/techniques, infrastructure and existing facilities of schools, are the major factors that affect to use the supplementary materials successfully in classrooms.